Monitoring the efficacy of a field-based heat acclimatization protocol to improve performance in elite female soccer players - Bowman, K. (University of British Columbia, 2018)
The purpose of this study was to investigate the efficacy of a 14-day, two-phase, field-based heat acclimatization (HA) training camp in international female soccer players. Sixteen outfield players engaged in (i) baseline absolute Plasma volume (PV) testing in Vancouver, Canada (~15°C; 72.0% relative humidity: RH) 16 days prior to the start of the camp, (ii) Phase 1: 7 days of pre-HA (22.1±3.3°C; 44.8±9.4%RH), (iii) Phase 2: 6 days of HA (34.5±1.2°C; 53.2±4.3%RH), and (iv) 11 days of post-HA training (18.2±4.6°C; 51.3±20.9%RH). Change in PV (%) from baseline was measured at the start of Phase 1, the end of Phase 1, and two days post-Phase 2. Core temperature (Tc), heart rate (HR), rate of perceived exertion (RPE), and Global Positioning System (GPS) derived metrics were recorded during all sessions. The physiological change during 5`-1` submaximal running (12km/h) was observed pre and post Phase 1 and 2, two days post Phase 2 (2dayP), and eleven days post Phase 2 (11dayP) using HR during exercise (HRex) and recovery (HRR), as well as RPE. GPS metrics, HRR, and HRex during a four-a-side soccer game (4v4SSG) were used to observe physical performance in the heat pre and post Phase 2. All data were analyzed using magnitude-based inference statistics. PV increased by 7.4±3.6% (Standardized effect; SE=0.63) from the start of Phase 1 to the end of Phase 2, and this occurred primarily in Phase 1 (SE=0.64). 5`-1` submaximal running improved over Phase 2 in hot conditions (HRex; SE= -0.49, HRR; SE=0.53). The greatest improvement in submaximal running in temperate conditions was delayed as the largest change from Phase 1 in HRex (SE= -0.42) and HRR (SE= 0.37) occurred 11dayP. The 4v4SSG revealed a moderate reduction in HRex (-3.5bpm), a large increase in HRR (5.7%), and a moderate increase in inertial explosive movements (20%) from pre to post Phase 2. Field-based HA can induce physiological change beneficial to soccer performance in temperate and hot conditions and the 5`-1` submaximal running test may be used to effectively monitor submaximal HR sponses that may have been induced by HA up to two-weeks out of the heat.